Evaluation of Hydrocarbon Source Rock Potential and Organic Geochemistry in North Arafura Shelf, Papua (Indonesia) - Eriko Sabra (Indonesian Journal on Geoscience, 2021)
DOI:10.17014/ijog.8.3.401-416The results of this study identified two potential source rock intervals of Permian age in the North Arafura Shelf area of Papua, Indonesia. The first potential source rock interval (SR-1) was identified at 3834.9 m to 3838.6 m depth within the Kola-1 well, which is believed to be good to very good potential source rock with TOC in the range of 2.94 to 3.4 wt %, S1 0.78 to 0.97 mg HC/g, and S2 5.63 to 9.5 mg HC/g. The source rock is composed of type II and III kerogens with HI in the range of 164 to 275 mg HC/gTOC and reached the maturation stage with Ro of 0.83 - 0.86%, Tmax of 442 - 444 C, and Production Index (PI) of 0.09 - 0.12. The second potential source rock interval (SR-2) is at 3060.1 - 3136.3 m depth in the ASM-1X well and has fair potential to be source rock with TOC of 0.95 wt %, S1 of 1.01 mg HC/g, and S2 of 3.39 mg HC/g. This source rock has type II kerogen with a HI value of 357 mg HC/g TOC and has reached maturation as indicated by a Ro value of 0.63%, Tmax of 430 C, and PI of 0.23. Biomarker analysis revealed SR-1 is type III kerogen with terrigenous input and was deposited in an estuarine environment.